2017
DOI: 10.1155/2017/5985703
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone Regulates Androgen Synthesis through the ERK/c‐Fos/CYP17 Pathway in Porcine Granulosa Cells

Abstract: The aim of the study is to investigate the molecular mechanism behind androgen reduction in porcine granulosa cells (pGCs) with Salvia miltiorrhiza Bunge extract cryptotanshinone. PGCs were isolated from porcine ovaries and identified. Androgen excess model of the pGCs was induced with the MAPK inhibitor PD98059 and then treated with cryptotanshinone. The testosterone level was measured by radioimmunoassay in the culture media. The protein levels of P-ERK1/2, c-Fos, and CYP17 in the cells were measured by west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Polycystic ovary syndrome (PCOS) is a common and disturbing endocrine disorder that affects approximately 7% of reproductive-aged women and is characterized by hyperandrogenism, ovulatory dysfunction, insulin resistance, polycystic ovarian morphology on ultrasound, weight gain, hirsutism, and other virilizing signs; hyperandrogenism is the main feature of PCOS [ 1 , 2 , 3 , 4 ]. According to previous reports, conditions of hyperandrogenic ovaries as well as adrenal androgen secretion appear to be upregulated in PCOS [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a common and disturbing endocrine disorder that affects approximately 7% of reproductive-aged women and is characterized by hyperandrogenism, ovulatory dysfunction, insulin resistance, polycystic ovarian morphology on ultrasound, weight gain, hirsutism, and other virilizing signs; hyperandrogenism is the main feature of PCOS [ 1 , 2 , 3 , 4 ]. According to previous reports, conditions of hyperandrogenic ovaries as well as adrenal androgen secretion appear to be upregulated in PCOS [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we detected potential regulatory mechanisms of CREBZF in apoptosis induction in ovarian granulosa cells. ERK1/2 activate cell cycle progression, mediate the mitogenic action of hormones and growth factors, stimulate ovarian cell proliferation, differentiation, and secretion activity [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], and suppress cell apoptosis [ 39 , 40 , 41 , 42 ]. The ERK1/2 signaling pathway is regulated in the ovary [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it also has a certain regulatory effect on androgen secretion. Previous studies have shown that Tanshinone can not only regulate the expression of key enzymes related to androgen biosynthesis but also regulate extracellular signal-regulated kinase (ERK)/C-FOS/17, 20-lyase (CYP17), leading to androgen biosynthesis levels being down [ 118 , 119 ]. However, it is worth noting that, in addition to having similar pharmacological effects, Tanshinone has other advantages over existing anti-male drugs.…”
Section: Molecular Targets Of Tanshinone Actionmentioning
confidence: 99%